The Digital Business Ecosystem and Its Implications for Local-Based Tourism Development in North Tapanuli - Simatupang, Jeslin; Situmorang, Ezra Renisilva; Hutapea, Riris Hertanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid expansion of digital technologies has reshaped the structure and dynamics of the tourism sector, particularly in destinations that rely on local economic and cultural resources. This study examines how digital business ecosystems influence the development of locally based tourism by focusing on digitally mediated interactions among local actors, platforms, and tourists. Employing a qualitative netnographic approach, the research analyzes publicly available online content from social media platforms, digital marketplaces, and travel-related online communities. The findings reveal that digital platforms function as central nodes that enable market access, value co-creation, and narrative construction for local tourism actors. Digital storytelling and interactive engagement enhance visibility and economic opportunities; however, benefits are uneven due to disparities in digital literacy, infrastructure, and platform dependency. The study also identifies socio-cultural implications, including increased cultural visibility alongside risks of commodification and misrepresentation. These findings highlight that digital transformation in tourism is not solely a technological process but a socio-economic and cultural one that requires inclusive governance and capacity-building. The study contributes to the literature on digital ecosystems and community-based tourism by providing empirical insights into how digitalization shapes local tourism development and sustainability.